Tracking the evolutionary pathway of sex chromosomes among fishes: characterizing the unique XX/XY1Y2 system in Hoplias malabaricus (Teleostei, Characiformes) - de Oliveira, Ezequiel Aguiar; Sember, Alexandr; Bertollo, Luiz Antonio Carlos; Yano, Cassia Fernanda; Ezaz, Tariq; Moreira-Filho, Orlando; Hatanaka, Terumi; Trifonov, Vladimir; Liehr, Thomas; Al-Rikabi, Ahmed Basheer Hamid; Ráb, Petr; Pains, Hugmar; et al. (Chromosoma, 2018)
The Neotropical fish, Hoplias malabaricus, is one of the most cytogenetically studied fish taxon with seven distinct karyomorphs (A-G) comprising varying degrees of sex chromosome differentiation, ranging from homomorphic to highly differentiated simple and multiple sex chromosomes. Therefore, this fish offers a unique opportunity to track evolutionary mechanisms standing behind the sex chromosome evolution and differentiation. Here, we focused on a high-resolution cytogenetic characterization of the unique XX/XY1Y2 multiple sex chromosome system found in one of its karyomorphs (G). For this, we applied a suite of conventional (Giemsa-staining, C-banding) and molecular cytogenetic approaches, including fluorescence in situ hybridization FISH (with 5S and 18S rDNAs, 10 microsatellite motifs and telomeric (TTAGGG) n sequences as probes), comparative genomic hybridization (CGH), and whole chromosome painting (WCP). In addition, we performed comparative analyses with other Erythrinidae species to discover the evolutionary origin of this unique karyomorph G-specific XY1Y2 multiple sex chromosome system. WCP experiments confirmed the homology between these multiple sex chromosomes and the nascent XX/XY sex system found in the karyomorph F, but disproved a homology with those of karyomorphs A-D and other closely related species. Besides, the putative origin of such XY1Y2 system by rearrangements of several chromosome pairs from an ancestral karyotype was also highlighted. In addition, clear identification of a male-specific region on the Y1 chromosome suggested a differential pattern of repetitive sequences accumulation. The present data suggested the origin of this unique XY1Y2 sex system, revealing evidences for the high level of plasticity of sex chromosome differentiation within the Erythrinidae.
Keywords: Sex Chromosomes; Male; pohlavní chromozomy; srovnávací genomová hybridizace; hybridizace in situ fluorescenční; mikrosatelitní repetice; Chromosome Painting; Repetitive Sequences, Nucleic Acid; Telomere; molekulární evoluce; karyotyp; Evolution, Molecular; mužské pohlaví; Repetitive sequences; Fish cytogenetics; ryby; Fishes; Male-specific region; Microsatellite Repeats; Animals; ženské pohlaví; telomery; zvířata; Comparative Genomic Hybridization; Whole chromosome painting; repetitivní sekvence nukleových kyselin; In Situ Hybridization, Fluorescence; Female; Karyotype; Comparative genomic hybridization; malování chromozomů